The Purpose of This Study Was to Improve Students' Critical Thinking Skills in The Civics Muple in Graduate Sentences in Class 4 - Cahyo Kurmai Setiyawan (Universitas Sebelas Maret, 2020)
The purpose of this study was to improve students' critical thinking skills in Civics muple class IV with the Think Pair Share Type Cooperative learning model. The research conducted was two cycles of Class Action Research (CAR), with each cycle consisting of one meeting. The stages of each cycle are planning, implementing, observing and reflecting. Each meeting is carried out a pre test and post test to determine the progress of students. In the first cycle students who completed after carrying out the post test were 58%. In the second cycle students who completed after carrying out the post test were 75%. These results indicate that the application of the Think Pair Share Type Cooperative model can improve student learning outcomes, especially Civics muple at SD Negeri 2 Besuki.